A Functional Allele of CsFUL1 Regulates Fruit Length through Repressing CsSUP and Inhibiting Auxin Transport in Cucumber. Issue 6 (12th April 2019) - Zhao, Jianyu; Jiang, Li; Che, Gen; Pan, Yupeng; Li, Yanqiang; Hou, Yu; Zhao, Wensheng; Zhong, Yanting; Ding, Lian; Yan, Shuangshuang; Sun, Chengzhen; Liu, Renyi; et al.
Abstract : A functional allele of FRUITFULL MADS-box ( CsFUL1 ) gene regulates fruit length by inhibiting the activity of CsSUP and auxin transporters CsPIN1 / 7 in cucumber. Abstract: Fruit length is a prominent agricultural trait during cucumber ( Cucumis sativus ) domestication and diversifying selection; however, the regulatory mechanisms of fruit elongation remain elusive. We identified two alleles of the FRUITFULL ( FUL )–like MADS-box gene CsFUL1 with 3393 C/A Single Nucleotide Polymorphism variation among 150 cucumber lines. Whereas CsFUL1 A was specifically enriched in the long-fruited East Asian type cucumbers (China and Japan), the CsFUL1 C allele was randomly distributed in cucumber populations, including wild and semiwild cucumbers. CsFUL1 A knockdown led to further fruit elongation in cucumber, whereas elevated expression of CsFUL1 A resulted in significantly shorter fruits. No effect on fruit elongation was detected when CsFUL1 C expression was modulated, suggesting that CsFUL1 A is a gain-of-function allele in long-fruited cucumber that acts as a repressor during diversifying selection of East Asian cucumbers. Furthermore, CsFUL1 A binds to the CArG-box in the promoter region of SUPERMAN, a regulator of cell division and expansion, to repress its expression. Additionally, CsFUL1 A inhibits the expression of auxin transporters PIN-FORMED1 ( PIN1 ) and PIN7, resulting in decreases in auxin accumulation in fruits. Together, our work identifies an agriculturally important allele and suggests a strategy for manipulating fruit length in cucumber breeding that involves modulation of CsFUL1 A expression.